Design and validation of an Index to predict the development of Hypertensive Cardiopathy - Álvarez-Aliaga, Alexis; Quesada-Vázquez, Andrés José; Suárez-Quesada, Alexis; Llano Sosa, David de (Journal of Cardiology and Cardiovascular Medicine, 2018)
Introduction: The high morbidity and mortality by hypertensive cardiopathy demand the construction and validation of tools to stratify the risk of developing this condition. Objective: To design and validate an index, based on risk factors, that permits to predict the development of hypertensive cardiopathy in patients with a diagnosis of essential arterial hypertension. Methods: A prospective cohort study was done in hypertensive patients assisted at the specialized arterial hypertension physicians’ office of the “Carlos Manuel de Céspedes” Specialty Policlinic attached to the General University Hospital, Bayamo Municipality, Granma Province, Cuba from January 1st, 2010 to December 31, 2016. Internal and external validity and the internal consistency of the index were determined. Results: The index sensitivity was of 97, 20 (IC: 93, 93-94.09) and specificity of 65, 38 (IC: 76, 25-76, 20). Both the index discriminative capacity (area under the ROC curve= 0,944; interval of confidence: 0.932-0.956; p<0.0005) and calibration (p=0.751) were adequate. Conclusions: The present study proposes an index to predict the risk of developing hypertensive cardiopathy, with adequate discriminative capacity and calibration (external validity). The index can be used as a tool of clinical and epidemiological surveillance since it permits to identify subjects with greater probability of developing the condition and to stratify the risk.